Molasses protected palm kernel cake as source of protein for young male Ettawah Grade goats - ., Supriyati; Haryanto, B (Indonesian Journal of Animal and Veterinary Sciences, 2011)
Palm kernel cake has a relatively high protein content, however its degradability in the rumen is high resulting in loosing its function as protein source for ruminant. This experiment was aimed toinvestigate the effect of feeding molasses protected palm kernel cake (BIS-M) on growth of young male Ettawah Grade (Peranakan Etawah = PE) goat. Twenty four (24) PE goats were divided into 4 groups and allocated to respective feeding BIS-M treatments. The treatments were R0 = control (without BIS-M), R1 = 15% BIS-M, R2 = 30% BIS-M and R3 = 45% BIS-M. The concentrate was fed at 400 gh-1d-1 for each individual in all treatment groups, while napier grass (Pennisetum purpureum) was offered ad libitum. The live weight of the goats were between 17-18 kg at the beginning of experiment. Feeding trial was carried out for 14 weeks consisting of 2 weeks for preliminary and 12 weeks for growth performance period. The digestibility study of the nutrient was carried out during the last 7 days ofÂ  the experiment. The experiment was arranged in a completely randomized design with 6 replications. Drinking water was available at any time. Feed intake was recorded daily while the body weight was recorded every 2 weeks. The parameters of observation were feed intake, live weight gain, nutrient digestibility and feed conversion ratio. The results indicated that the dietary treatments affected the intake and digestibility of nutrients, average daily gain and feed conversion ratio (P < 0.05). The total feed dry matter intakes were 599,30; 620,74; 690,19 and 740,04 gh-1d-1 with DM and Protein digestibility of 64.74 and 75.99; 67.47 and 73.05; 70.06 and 73.02; and 72.88 and 72.25% respectively for R0, R1, R2 and R3. The ADG were 42.06; 52.78; 61.90 and 70.24 g; with feed conversion ratio of 14.68; 10.51; 9.08; and 9.85 for R0, R1, R2 and R3. It was concluded that BIS-M can be used as source of protein with optimal utilization level at 30% of the concentrate. Key Words: Palm Kernel Cake, Molasses, Ettawah Grade goats, Performance